2019
DOI: 10.14302/issn.2374-9431.jbd-19-2613
|View full text |Cite
|
Sign up to set email alerts
|

Trigonella Foenum Graecum Extract Benefits on Hematological, Biochemical and Male Reproductive System of as a Complementary Therapy with Glimepiride in Treating Streptozotocin Induced Diabetic Rats

Abstract: Diabetes mellitus (DM) is a chronic metabolic disorder. Streptozotocin is a naturally occurring cytotoxic chemical, particularly toxic to the pancreas and insulin producing beta cells in mammals and induces diabetes. Glimepiride is a second generation sulfonylurea, used as second-line or add-on treatment options for type 2 diabetes. Fenugreek (Trigonellafoenum graecum) seeds have been documented as a traditional plant treatment for diabetes. Soluble dietary fiber of Fenugreek significantly improved oral glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In the present study, the rats which treated with fennel herb indicates significant increase in the antioxidant, this results agreed with Kooti et al [72] reported that medicinal herbs have fewer side effects than synthetic drugs and due to their antioxidant properties they reduce drugs toxicity. The natural effective ingredients cause biological balance and prevent drug accumulation in body [73,18]. Medicinal plants can be used in the treatment of various diseases [72,18].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the rats which treated with fennel herb indicates significant increase in the antioxidant, this results agreed with Kooti et al [72] reported that medicinal herbs have fewer side effects than synthetic drugs and due to their antioxidant properties they reduce drugs toxicity. The natural effective ingredients cause biological balance and prevent drug accumulation in body [73,18]. Medicinal plants can be used in the treatment of various diseases [72,18].…”
Section: Discussionmentioning
confidence: 99%
“…The glomeruli are reduced as a result of these modifications[52]. The diabetic rats displayed glomerular shrinkage, tubular casts, and inflammatory cellular infiltration[52]. Rats on a high-fat diet for two weeks displayed more inflammatory cells, cardiac muscle fibers in decline, and round and clogged blood arteries[53].Conclusion: Based on our findings, avocado fruit extract has a powerful ameliorative role against MSGinduced nephrotoxicity in pregnant rats and their neonates.…”
mentioning
confidence: 68%
“…Diabetic rats' kidney tissue exhibited enlarged basement membranes of the proximal and distal convoluted tubules, increased glycogen deposition, and increased mesangial cell and matrix of glomeruli. The glomeruli are reduced as a result of these modifications[52]. The diabetic rats displayed glomerular shrinkage, tubular casts, and inflammatory cellular infiltration[52].…”
mentioning
confidence: 99%
“…Kidney sections of diabetic rats showed an increase in mesangial cells and matrix of glomeruli with an increase in glycogen deposition and hyalinization of arteries with thickened basement membranes of proximal and distal convoluted tubules. These changes lead to a reduction in the glomeruli (Elghazaly et al, 2019b). The diabetic rats showed tubular casts, inflammatory cellular infiltration and glomerular atrophy (Elghazaly et al, 2019b).…”
Section: Treatmentmentioning
confidence: 99%
“…These changes lead to a reduction in the glomeruli (Elghazaly et al, 2019b). The diabetic rats showed tubular casts, inflammatory cellular infiltration and glomerular atrophy (Elghazaly et al, 2019b).…”
Section: Treatmentmentioning
confidence: 99%